Using in situ airborne measurements to evaluate three cloud phase products derived from CALIPSO. Issue 10 (17th May 2016) - Cesana, G.; Chepfer, H.; Winker, D.; Getzewich, B.; Cai, X.; Jourdan, O.; Mioche, G.; Okamoto, H.; Hagihara, Y.; Noel, V.; Reverdy, M.
Abstract: We compare the cloud detection and cloud phase determination of three independent climatologies based on Cloud‐Aerosol Lidar and Infrared Pathfinder Satellite Observation (CALIPSO) to airborne in situ measurements. Our analysis of the cloud detection shows that the differences between the satellite and in situ measurements mainly arise from three factors. First, averaging CALIPSO Level l data along track before cloud detection increases the estimate of high‐ and low‐level cloud fractions. Second, the vertical averaging of Level 1 data before cloud detection tends to artificially increase the cloud vertical extent. Third, the differences in classification of fully attenuated pixels among the CALIPSO climatologies lead to differences in the low‐level Arctic cloud fractions. In another section, we compare the cloudy pixels detected by colocated in situ and satellite observations to study the cloud phase determination. At midlatitudes, retrievals of homogeneous high ice clouds by CALIPSO data sets are very robust (more than 94.6% of agreement with in situ). In the Arctic, where the cloud phase vertical variability is larger within a 480 m pixel, all climatologies show disagreements with the in situ measurements and CALIPSO‐General Circulation Models‐Oriented Cloud Product (GOCCP) report significant undefined‐phase clouds, which likely correspond to mixed‐phase clouds. In all CALIPSO products, the phase determination is dominated by the cloud top phase. Finally, we use global statistics to demonstrate that main differences between the CALIPSO cloud phase products stem from the cloud detection (horizontal averaging, fully attenuated pixels) rather than the cloud phase determination procedures. Key Points: Comparison of the cloud and cloud phase of three CALIPSO climatologies with in situ measurements Cloud detection differences due to vertical/horizontal averaging and fully attenuated pixels Very high agreement for midlatitude ice clouds, more disagreement with the mixed‐phase clouds